Intraosseous Pneumatocysts of the Scapula Mimicking Bone Tumors: A Report of Two Rare Cases Along with Elucidation of Their Etiology - Jiro Ichikawa; Masanori Wako; Tomonori Kawasaki; Satoshi Ochiai; Tetsuo Hagino; Naofumi Taniguchi; Kouhei Mitsui; Kojiro Onohara (Diseases)
Background/Objectives: Pneumatocysts, characterized by gas-filled cavities, are commonly found in the spine and pelvis but are rarely observed in the scapula. In this report, we describe two rare cases of scapular pneumatocysts mimicking bone tumors and exhibiting different image findings. Case Report: Case 1. A 47-year-old man who presented with neck pain underwent radiography, followed by magnetic resonance imaging (MRI). MRI showed heterogeneity with low and high signals on fat-suppressed T2-weighted images, suggestive of enchondroma or fibrous dysplasia (FD). However, preoperative computed tomography (CT) revealed gas-filled cavities within the tumor, in continuity with the shoulder joint, confirming the diagnosis of a pneumatocyst. Case 2. A 58-year-old woman who presented with neck pain underwent similar examinations to Case 1. MRI showed homogeneity with high signals on fat-suppressed T2-weighted images, leading to a suspicion of solitary bone cysts and FD. Preoperative CT revealed gas-filled cavities within the tumor, but no continuity with the joint, leading to the diagnosis of a pneumatocyst. While the exact etiology of pneumatocysts remains unclear, two potential causes are as follows: (i) gas migration from the joint to the bone, and (ii) gas replacement in cystic tumors. Thus, CT is particularly valuable in confirming the presence of gas-filled cavities and aiding in diagnosis. Conclusions: This report highlights two extremely rare cases of scapular pneumatocysts, reflecting two potential etiologies. The utility of CT in the diagnosis of pneumatocyst has been clarified.